STUDI TENTANG KEPADATAN, KELIMPAHAN DAN POLA PENYEBAR IKAN LAYUR (Trichiurus lepturus L) PADA PERAIRAN DESA PASSO TELUK BAGUALA AMBON - Pieter Siahaya; Dominggus Rumahlatu (Program Studi Pendidikan Biologi FKIP Unpatti, 2015)
Background: Fish layur which is often called the people of Maluku as Fish Parang-parang is included order Perciformes in the Trchiuridae family and genus Trichiurus. The existence of fish in the waters Layur Passo not known with certainty. Methods: The study took place in October 2014. The study was divided into three locations of the research station. The method used in this study are visual census to calculate directly the large number of fish caught at the sites. Then the data were analyzed descriptively. Calculations used in the processing of the data using the formula of density, abundance, and distribution patterns. Environmental characteristics in measuring temperature, salinity, pH, and dissolved oxygen (DO). Results: The results showed that the water environmental condition Passo village is quite good for the survival of the organism. Conclusion: The density, abundance, and distribution pattern of fish layur relatively abundant in these waters with the highest value contained at two stations at the sites.